Sensorimotor Reorganizations of Arm Kinematics and Postural Strategy for Functional Whole-Body Reaching Movements in Microgravity - Macaluso, Thomas; Bourdin, Christophe; Buloup, Frank; Mille, Marie-Laure; Sainton, Patrick; Sarlegna, Fabrice R.; Vercher, Jean-Louis; Bringoux, Lionel (Frontiers in Physiology, 2017)
Understanding the impact of weightlessness on human behavior during the forthcoming long-term space missions is of critical importance, especially when considering the efficiency of goal-directed movements in these unusual environments. Several studies provided a large set of evidence that gravity is taken into account during the planning stage of arm reaching movements to optimally anticipate its consequence upon the moving limbs. However, less is known about sensorimotor changes required to face weightless environments when individuals have to perform fast and accurate goal-directed actions with whole-body displacement. We thus aimed at characterizing kinematic features of whole-body reaching movements in microgravity, involving high spatiotemporal constraints of execution, to question whether and how humans are able to maintain the performance of a functional behavior in the standards of normogravity execution. Seven participants were asked to reach as fast and as accurately as possible visual targets while standing during microgravity episodes in parabolic flight. Small and large targets were presented either close or far from the participants (requiring, in the latter case, additional whole-body displacement). Results reported that participants successfully performed the reaching task with general temporal features of movement (e.g., movement speed) close to land observations. However, our analyses also demonstrated substantial kinematic changes related to the temporal structure of focal movement and the postural strategy to successfully perform -constrained- whole-body reaching movements in microgravity. These immediate reorganizations are likely achieved by rapidly taking into account the absence of gravity in motor preparation and execution (presumably from cues about body limbs unweighting). Specifically, when compared to normogravity, the arm deceleration phase substantially increased. Furthermore, greater whole-body forward displacements due to smaller trunk flexions occurred when reaching far targets in microgravity. Remarkably, these changes of focal kinematics and postural strategy appear close to those previously reported when participants performed the same task underwater with neutral buoyancy applied to body limbs. Overall, these novel findings reveal that humans are able to maintain the performance of functional goal-directed whole-body actions in weightlessness by successfully managing spatiotemporal constraints of execution in this unusual environment.